Gap junction enhancer as an anti-cancer agent via GJIC-independent and -dependent pathways - Ding, Ying (Kansas State University, 2013)
Gap junctions (GJ) are intercellular channels connecting adjacent cells, allowing small molecules to transport between cells, thereby maintaining all homeostasis. Loss of gap junctional intercellular communication (GJIC) and/or connexins, the gap junction proteins, is a hallmark of cancer. Restoration of GJIC and/or increase of connexin expression have been related to the reduction of tumorigenesis. Connexins have been reported as tumor suppressors due to both GJIC-independent and -dependent mechanisms. Therefore, development of effective agents or methods to enhance GJIC and restore connexin expression in cancer cells is a new strategy in cancer treatment. PQ1, 6-Methoxy-8-[(3-aminopropyl)amino]-4-methyl-5-(3-trifluoromethyl-phenyloxy)quinoline, has been demonstrated to increase GJIC, restore connexin expression, and exert anti-cancer effects on T47D breast cancer cells. Studies of apoptotic pathways showed that PQ1 activated both extrinsic and intrinsic apoptotic pathways, indicating that PQ1 exerts its anti-cancer effects via a GJIC-independent mechanism through the induction of apoptosis. Combinational treatment of PQ1 and cisplatin showed that PQ1 counteracted cisplatin-induced inhibition of GJIC and reduction of connexin expression, thereby increasing the efficacy of cisplatin in T47D cancer cells via a GJIC-dependent mechanism. Further studies of drug distribution and toxicity revealed that administration of PQ1 by oral gavage can be achieved with low toxicity to normal vital organs. All the results suggest that PQ1, a gap junction enhancer, can function as an anti-cancer agent and potentiate the efficacy of antineoplastic drugs via both GJIC-independent and -dependent pathways.
Keywords: Gap junction; Breast cancer; PQ1; Quinoline derivative; Biochemistry (0487); Molecular Biology (0307)